Vai trò trung gian của động lực nội sinh và ngoại sinh trong mối quan hệ giữa yêu cầu công việc thách thức và hiệu quả công việc: Trường hợp nhân viên thị trường bất động sản Việt Nam - Phạm Minh, Luân; Nguyễn Thị Mai , Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This study examines the relationship between challenge demands and task performance. This relationship is mediated by intrinsic motivation and extrinsic motivation. With 215 real estate salespeople, findings demonstrate that challenge demands were positively related to intrinsic motivation and extrinsic motivation, both of which were in turn positively affected task performance. However, challenge demands were not related to task performance. This also showed that intrinsic motivation and extrinsic motivation were full mediators in the above relationships.